2021
DOI: 10.1186/s12967-021-02877-4
|View full text |Cite
|
Sign up to set email alerts
|

eIF6 promotes the malignant progression of human hepatocellular carcinoma via the mTOR signaling pathway

Abstract: Background Eukaryotic translation initiation factor 6 (eIF6) has a crucial function in the maturation of 60S ribosomal subunits, and it controls the initiation of protein translation. Although emerging studies indicate that eIF6 is aberrantly expressed in various types of cancers, the functions and underlying molecular mechanisms of eIF6 in the pathological progression of hepatocellular carcinoma (HCC) remain unclear. This study aimed to evaluate the potential diagnostic and prognostic value of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…4EBP1 and p70S6K axes play critical and distinct roles in hepatocarcinogenesis 36 . The target genes of the mTOR pathway, such as MYC, Cyclin D1, HIF1α, and SREBP1, participate in many malignant behaviors of HCC cells 37 - 39 . Recent studies report that glutamine synthetase (GS), a transcriptional target of β-catenin, functions as a driver in HCC development by promoting p-mTOR (S2448) expression 40 - 42 .…”
Section: Discussionmentioning
confidence: 99%
“…4EBP1 and p70S6K axes play critical and distinct roles in hepatocarcinogenesis 36 . The target genes of the mTOR pathway, such as MYC, Cyclin D1, HIF1α, and SREBP1, participate in many malignant behaviors of HCC cells 37 - 39 . Recent studies report that glutamine synthetase (GS), a transcriptional target of β-catenin, functions as a driver in HCC development by promoting p-mTOR (S2448) expression 40 - 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to conclude that eIF6 is a critical regulator of tumor growth. Additionally, this hypothesis has also been proven because eIF6 knock-down could efficiently inhibit the progression of hepatocellular carcinoma and non-small cell lung carcinoma ( 21 , 24 ). Since it has been reported that eIF6 is essential for immune system homeostasis in both mice and humans, we also investigated the tumor immunology of eIF6.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the skin melanoma samples exhibited significantly increased eIF6 expression levels than the normal skin samples, corresponding to the up-regulated melanoma cells division rates ( Figure 1 ). Earlier studies have suggested that eIF6 is up-regulation in hepatocellular carcinoma, lung adenocarcinoma, and colorectal cancer ( 21 , 23 , 24 ). Similarly, the increased eIF6 expression levels also could be observed in LGG and PAAD using the GEPIA database analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations